The influence of heterogeneity of lacustrine shale facies on rock mechanical properties and brittleness: a case study of Jurassic lacustrine shale reservoirs in Northeast Sichuan Basin - Zhao, Haibo; Yin, Shujun; Yang, Xuefeng; Yan, Weilin; Bi, Guangwu; Zhang, Jianliang; Xing, Zimeng (Frontiers in Earth Science, 2025)
IntroductionDue to the significant increase in plasticity under conditions of high temperature and pressure, the existing single brittleness evaluation methods prove inadequate for accurately characterizing the compressibility of deep shale in northeastern Sichuan, thereby severely limiting the optimal target selection and engineering modification in this region.MethodsThe focus of this paper is the deep Jurassic shale in northeastern Sichuan, studied through triaxial high-temperature and high-pressure tests, tensile tests, and X-ray diffraction experiments, which examine the mechanical properties of shale and the factors influencing them. The morphological characteristics of rock fractures under various loading conditions are analyzed, providing a standard for assessing brittleness factors and conducting a comprehensive quantitative evaluation.ResultsThe research concludes that the deep lacustrine shale exhibits traits of high elastic modulus and high Poisson’s ratio, with its brittleness largely influenced by mineral composition, the development characteristics of lamination, the degree of lamination development, and the anisotropy of the rock. Crack patterns have been analyzed to investigate the morphology of rock fractures. Through a correlation analysis of normalized rock parameters and the brittleness index derived from stress-strain curves with the fracture breakdown pressure and extension pressure observed in field fracturing, a comprehensive evaluation index has been established using the analytic hierarchy process to reflect the brittleness of deep lacustrine shale.DiscussionThis index serves effectively in characterizing the brittleness features of deep lacustrine shale, and evaluations suggest that the Liang upper section has a relatively high brittleness index and good compressibility, marking it as a key target layer for future shale gas development.